Anti-Money Laundering A Comparative and Critical Analysis of the UK and UAE's Financial Intelligence Units - Alhosani, Waleed; SpringerLink (Online service) (London : Palgrave Macmillan UK (Imprint), 2016)
This book critically analyses the role of the United Arab Emirates Financial Intelligence Unit (FIU) in the Suspicious Activities Reports regime. The author pays particular attention to its functions and powers in dealing with Suspicious Activities Reports and relevant requirements imposed upon the reporting entities. In the analysis, the author also compares the United Arab Emirates FIU model to the United Kingdom FIU model. In addition, the book investigates whether the current United Arab Emirates FIU model complies with the relevant international recommendations developed by the Financial Action Task Force in relation to the establishment of the unit, as well as its powers and functions. This book suggests that more can be done to improve the current functions and powers of the United Arab Emirates FIU in an international context. Furthermore, the author suggests that the functions and powers of the United FIU model both comply with the international requirements and beneficially extend beyond their directives. .
1) Introduction -- 2) Literature Review -- 3) Banking confidentiality versus disclosure -- 4) The Nature of the FIU from the Perspective of International Standards -- 5) The Emergence of the United Arab Emirates' FIU in Counteracting Money Laundering -- 6) Empirical Investigation in Relation to the AMLSCU -- 7) The United Kingdom's Anti-Money Laundering Legislation and System -- 8) The United Kingdom's SARS Regime on Money Laundering -- 9) The Role of the SOCA, Now the NCA, in the SARS Regime -- 10) Recommendations and Conclusion.
Keywords: Corporations-Finance.; Finance, Public; Financial Law/Fiscal Law; Private International Law, International & Foreign Law, Comparative Law